2020
DOI: 10.1096/fj.202001510r
|View full text |Cite
|
Sign up to set email alerts
|

EphA4 regulates Aβ production via BACE1 expression in neurons

Abstract: Several lines of evidence suggest that the aggregation and deposition of amyloid-β peptide (Aβ) initiate the pathology of Alzheimer's disease (AD). Recently, a genomewide association study demonstrated that a single-nucleotide polymorphism proximal to the EPHA4 gene, which encodes a receptor tyrosine kinase, is associated with AD risk. However, the molecular mechanism of EphA4 in the pathogenesis of AD, particularly in Aβ production, remains unknown. Here, we performed several pharmacological and biological ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Apart from neurotransmission-associated molecular functions, molecular functional pathway analysis revealed this list to be significantly enriched for genes defined as “amyloid-beta binding” (fold enrichment = 7.79, p (FDR) = 0.01) ( Fig. 3A ), including SORL1 , an endocytic receptor that directs the amyloid precursor protein away from the amyloidogenic pathway (4345) and EPHA4 , a receptor tyrosine kinase involved in amyloid regulation (46). Since α5-containing nicotinic receptors are highly permeable to calcium ions (21,22), we note that chandelier neurons are also significantly enriched for genes with a “calcium ion binding” molecular function (fold enrichment = 3.77, p (FDR) = 4.12*10 −6 ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from neurotransmission-associated molecular functions, molecular functional pathway analysis revealed this list to be significantly enriched for genes defined as “amyloid-beta binding” (fold enrichment = 7.79, p (FDR) = 0.01) ( Fig. 3A ), including SORL1 , an endocytic receptor that directs the amyloid precursor protein away from the amyloidogenic pathway (4345) and EPHA4 , a receptor tyrosine kinase involved in amyloid regulation (46). Since α5-containing nicotinic receptors are highly permeable to calcium ions (21,22), we note that chandelier neurons are also significantly enriched for genes with a “calcium ion binding” molecular function (fold enrichment = 3.77, p (FDR) = 4.12*10 −6 ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It further added that the expression level of EphA‐4 decreases in the transgenic murine model of AD before the onset of cognitive impairment (Simón et al, 2009). Recently, Tamura et al (2020) observed that the expression of EphA‐4 declines with AD that correlated negatively with the level of the BACE1 gene.…”
Section: The Pathophysiology Of Ad Due To Ephrine Receptorsmentioning
confidence: 99%
“…Surprisingly, several reports exist that support the protective role of EphA‐4 in AD pathogenesis. For example, pharmacological and genetic ablation of EphA‐4 leads to an increase in the expression of BACE1, an enzyme responsible for producing Aβ (Tamura et al, 2020). EphA‐4 signalling in a platelet‐derived growth factor receptor β (PDGFRβ) dependent manner promotes the proliferation of neural progenitor cells (NPCs) and alleviates cognitive impairment in a murine transgenic AD model (Chen et al, 2020).…”
Section: The Pathophysiology Of Ad Due To Ephrine Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…BIN1 and EphA4 are genetic risk factors for Alzheimer’s disease that mediate Aβ production via regulation of BACE1 transport and activity. 24 , 25 These findings motivated the development and testing of BACE1 inhibitors in drug trials, without reaching treatment endpoints and with indications of negative cognitive effects, other adverse effects, including regionally increased brain atrophy. 26–29 Side effects of BACE1 inhibitors are both on-target and off-target, and specificity for BACE1 inhibitors tested in clinical trials is also limited.…”
Section: Introductionmentioning
confidence: 99%